Implementation of ArcGIS story maps as a media information and counseling of COVID-19 in palu city - Suni, Muhammad Adam; Muis, Hasriani (Journal of Soft Computing Exploration, 2023)
The COVID-19 pandemic continues to increase, transmission, spread, and death rates are increasing, resulting in the implementation of large-scale social restrictions on community activities in Indonesia. This high rate of transmission can be caused by poor public behavior towards prevention programs that have been announced by the Government. In order to increase public knowledge in prevention and communication and minimize the spread of COVID-19, socialization and outreach media are needed that can encourage more effective delivery and dissemination of information. Technological developments encourage the delivery of information to become more interactive. One use of technology is delivering information with spatial integration through ArcGIS Story Maps. Story Maps can be handy for spreading knowledge on several topics, focusing on where the story occurs. In this paper, we explore the opportunities offered by Story Maps to implement Story Maps as an outreach media and a solution for socializing and disseminating information during the pandemic. Specifically, we refer to a series of different applications offered by Esri for building Story Maps based on different approaches and techniques. The results of using Story Maps are in the form of presenting information, information media, and counseling in the form of an interactive map which contains a general description of COVID-19, case conditions, level of spread, and how to handle it and related regulations through the Story Maps feature. This story map involves geospatial elements, web GIS, text, images, and video so that it can be an alternative solution for related parties in socializing and disseminating information during the pandemic